Pengaruh jumlah sudu dan diameter nozel terhadap kinerja turbin pelton - Mafruddin Mafruddin; Rully Meygi Irawan; Nanang Setiawan; Nurlaila Rajabiah; Dwi Irawan (TURBO [Tulisan Riset Berbasis Online], 2019)
Pelton turbine is one type of impulse turbine that is commonly used in hydroelectric power plants such as micro hydropower plants. The choice of the turbine is based on the high-efficiency generated by the pelton turbine. The main components of the pelton turbine are blades and nozzles. The purpose of this study was to determine the amount of blade and nozzle diameter on the performance of the pelton turbine. The research method was carried out experimentally by design and manufacture of a pelton turbine prototype. Turbines made and protected have specifications of a runner diameter of 150 mm, blade length of 31,1 mm, blade width of 14,6 mm, blade depth of 6,45 mm and number of nozzles 1 piece. From the results of the study note that the number of blades and diameter of the nozzles affect the power turbine. The highest turbine power is obtained using a number of 21 blades and 8 mm nozzle diameter of 2,15 Watts. Whereas with the number of blades 19 and 8 mm nozzle diameter, turbine power is 1,91 Watt, turbine power with 23 blades and 8 mm nozzle diameter is 1,95 Watts. Turbine power with 19 blades and 10 mm nozzle diameter is 1,4 Watts, turbine power with 21 nozzles and 10 mm nozzle diameter is 1,49 Watts and turbine power with 23 blades and 10 mm nozzle diameter is 1,41 Watts.Keywords: Number of blades, nozzle diameter, pelton turbine performance.